Accès aux services de santé en français et gouverne en réseau : différentes représentations et stratégies d'action - Collin, Stéphanie; Grenier, Gabrielle; McIntyre, Martine; Roy, Shanie (Revue Gouvernance, 2022)
Au Canada, l’enjeu de l’amélioration de l’accès aux services de santé en français, surtout dans les provinces hors Québec, s’inscrit dans des relations complexes entre différents acteurs qui poursuivent des objectifs variés. En 2008, au Nouveau-Brunswick, l’État a remplacé les huit régies régionales existantes par deux nouvelles régies, soit la Régie régionale de la santé A (Réseau de santé Vitalité) et la Régie régionale de la santé B (Réseau de santé Horizon). Plus tard, il a été établi que Vitalité fonctionnerait en français et Horizon en anglais, et que les réseaux assureraient la prestation des services de santé dans la langue officielle du choix des citoyens. Ainsi, l’objectif général de la recherche était de comprendre l’influence des dynamiques entre les acteurs d’une gouverne en réseau sur le traitement de l’enjeu que représente l’accès aux services de santé en français. Une méthode qualitative comprenant notamment des entretiens semi-directifs (n=26) a été retenue. Les résultats montrent que, d’une part, l’offre de services dans la langue du choix des citoyens, qui est conditionnée par le cadre juridique sur les droits linguistiques, pousse les acteurs à mobiliser des stratégies axées sur la qualité et la sécurité. D’autre part, l’accès révèle une dimension symbolique, puisqu’il est associé aux notions d’équité et de gouvernance. L’accès aux services de santé en français est un sujet délicat pour l’État, qui demeure en retrait par rapport à celui-ci. Afin de mieux répondre aux besoins en santé des citoyens, cet acteur doit faire émerger des liens de confiance et formuler des objectifs clairs. Mots-clés : gouverne, réseau, accès, santé, communautés francophones en situation minoritaire, langues officielles

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Repérage de quelques obstacles linguistiques et culturels des soins de santé pour les immigrants francophones de la Nouvelle-Écosse - Fontaine, Louise (Port Acadie, 2010)
Ce texte s’attarde au concept d’« immigrant francophone » appliqué au contexte de la Nouvelle-Écosse. Contrairement à ce qu’on peut imaginer à un premier niveau d’analyse, ce concept est polysémique et le sens qu’on y attribue varie selon les acteurs sociaux qui l’utilisent. Donc, afin de mieux délimiter l’objet de notre propos, nous avançons quelques éléments de définition à prendre en compte. Il s’agit d’une recherche exploratoire orientée vers la formulation de quelques pistes de réflexion, voire quelques hypothèses de travail à vérifier lors de la réalisation de futures recherches dans le domaine de la santé auprès des communautés francophones et acadiennes de la Nouvelle-Écosse. Pour étoffer notre propos, nous présentons quelques données empiriques recueillies à même le travail de terrain mené principalement dans le milieu associatif à Halifax et dans le sud-ouest de la province depuis 2003. Dans ce contexte, nous avons mené des enquêtes en procédant notamment à de l’observation participante. Nous avons aussi eu recours à des documents écrits tels que des documents gouvernementaux, des articles dans des revues spécialisées, des journaux. Les liens que nous avons établis entre des thèmes comme langue, culture et santé nous ont conduite finalement à proposer quelques questions de recherche et quelques hypothèses de travail.

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Immigration et santé. Où en sont les Francophones ? Une enquête sur l'état de santé des immigrants francophones en Colombie-Britannique - Poullos, Nichollos (RésoSanté Colombie-Britannique, 2018)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau de santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.